The link between corporate environmental performance and corporate financial performance - Eilola, Maria (2017)
The question of whether companies can do good by doing good has aroused a lot of interest among academics and company managers. The link between corporate social or environmental performance (CSP/CEP) and corporate financial performance (CFP) has been studied a lot – and with several different methods, in both directions and in different industries. Majority of earlier studies have found a positive link between CSP/CEP and CFP but due to challenges in measuring social and environmental performance, there is a lot of inconsistency in the study results. However, earlier studies clearly indicate that companies are not punished for their social and environmental efforts. The aim of this study was to examine the link between corporate environmental performance (CEP) and corporate financial performance (CFP) in the forest, paper and packaging industry and in the manufacturing of machinery and equipment industry. The study was conducted as a qualitative study although it includes also some quantitative elements. Data consisted of CEP disclosures, mainly corporate social responsibility reports and annual reports. There were five target companies. Environmental data evaluation criteria were developed specifically for this study by utilizing several sources, such as KLD rating framework and GRI reporting framework. Corporate environmental performance of the five target companies was analysed by using content analysis method. Return on equity figures were used as indicators of corporate financial performance. The link was evaluated by utilizing statistical computing. Pearson’s correlation coefficiencies were computed for CEP and CFP figure pairs. Differing from majority of earlier studies, this study indicates that there is no link between CEP and CFP – not from CEP to CFP nor CFP to CEP. Correlation coefficiency figure is significant in some cases but as the figures varies greatly, strong correlation figures are likely caused by coincidence. From CEP to CFP, the correlation varied anywhere between -0.15 and 0.63. From CFP to to CEP, the correlation varied anywhere between -0.16 and 0.90. Although positive link was not found, the results indicate that companies are not punished for high environmental performance.